2020
DOI: 10.1101/2020.06.24.164988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global and local tension measurements in biomimetic skeletal muscle tissues reveals early mechanical homeostasis

Abstract: AbstractThe mechanical properties and tension of muscle tissue are tightly related to proper skeletal muscle function, which makes experimental access to the biomechanics of muscle tissue development a key requirement to advance our understanding of muscle function and development. Recently developed elastic in vitro culture chambers allow for raising 3D muscle tissue under controlled conditions and measurements of tissue force generation. However, th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 56 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…Typical values of muscle tension are 675 ± 123 Pa (mean ± SD, n=8) during single twitch stimulation, and 871 ± 114 Pa during tetanic stimulation. Other studies reported slightly higher twitch tensions between 1-2 kPa for micro-tissues grown from C2C12 skeletal muscle cells (20,21), and 1.7 kPa for micro-tissues grown from satellite cells (35). For comparison, intact soleus (SOL) and extensor digitorum longus (EDL) muscles of young/adult mice generate tetanic tensions of around 150-220 kPa (SOL) and 200-240 kPa (EDL), respectively (37)(38)(39).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Typical values of muscle tension are 675 ± 123 Pa (mean ± SD, n=8) during single twitch stimulation, and 871 ± 114 Pa during tetanic stimulation. Other studies reported slightly higher twitch tensions between 1-2 kPa for micro-tissues grown from C2C12 skeletal muscle cells (20,21), and 1.7 kPa for micro-tissues grown from satellite cells (35). For comparison, intact soleus (SOL) and extensor digitorum longus (EDL) muscles of young/adult mice generate tetanic tensions of around 150-220 kPa (SOL) and 200-240 kPa (EDL), respectively (37)(38)(39).…”
Section: Discussionmentioning
confidence: 98%
“…The force generation of this tissue can be measured by the deflection of the flexible pillars. 3-D microtissues grown from skeletal muscle cell sources can thus be used as a platform for studying physiological and mechanical properties of muscles (20,21), for drug testing (22,23), and for disease modeling (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…As recently reported, all of these cell lines are capable of forming functional biomimetic skeletal muscle tissues within 3D protein scaffolds by self-organizing around two vertical posts [42,17] . With these human immortalized myoblast cell lines from healthy and DMD backgrounds, and our previously developed glass bottom chamber for high resolution imaging [22] , we cultured bioengineered skeletal muscles within a 3D fibrin-Geltrex™ scaffold over two weeks (Figure 1 a-d). All of the human immortalized cell lines self-organized nicely to form tissues around the two posts (Figure 1 e).…”
Section: Myotube and Muscle Tissue Morphology Is Dependent On Dystrophinmentioning
confidence: 99%
“…Elastic beads as pressure sensors. A custom made 37 water-in-oil emulsion was used to prepare the inert PAA beads of Young's modulus E = 3.9 ± 0.9 kPa, by injecting the water-based bead mix in oil dissolved in n-Hexane (Supelco). The PAA beads were fluorescently labelled (Atto 488 NHS-Ester, Atto-Tec) several times until sufficient fluorescent signal was achieved.…”
Section: Mean Squared Displacement (Msd)mentioning
confidence: 99%